Rockfall Analysis and Optimized Design of Rockfall Barrier Along a Strategic Road near Solang Valley, Himachal Pradesh, India - Verma A.K.; Sardana S.; Singh T.N.; Kumar N. (My University, 2025)
In the Himalayan region, roadways, railways, power plants, buildings and other houses are prone to rock falls. Considering the rockfall risk in the Himalaya, this study focuses on an under construction route for Manali–Leh highway along Solang–Rohtang tunnel in Himachal Pradesh. The slopes along this road are unstable and prone to rockfall. Soon with the completion of Rohtang tunnel, this road will hit a huge amount of traffic, as it will be the shortest route to the Lahaul Spiti. So, the detailed assessment of rockfall hazard along this road is necessary. In the present study, rockfall simulation has been carried out to determine the parameters such as bounce height, maximum run-out distance, energy and velocity associated with falling rock blocks on the basis of field and laboratory analysis. The bounce height and the kinetic energy were found to be greater than 5 m and 50 kJ, respectively, in the analysis. The optimization of the ditch, slope geometry and the design of rockfall barrier have been performed duly taking slope parameters into consideration. The result shows that the optimized ditch is effective to arrest the larger number of falling rock blocks and also the kinetic energy of the rock block can be decreased by performing slope trimming. A standard barrier of 100 kJ capacity and 2.5 m height has been found suitable and proposed to make the roadway along this highway safer for travellers. © 2018, Indian Geotechnical Society.